The Application Of Guided Inquiry Learning In Improving The Mastery Of Concepts And Science Process Skills On Vibration And Wave Material - Juliatriyani Juliatriyani; Leny Heliawati; Surti Kurniasih (JSEP (Journal of Science Education and Practice), 2021)
This research is a research that uses a quasi-experimental method with a Nonequivalent Control Group Design which aims to increase the ability to master concepts and science process skills of students who study wave vibrations with a guided inquiry approach and students who study wave vibrations using the demonstration method. The population used in this study was all students of SMPN 4 Cibinong in the even semester of the 2016-2017 academic years. The researcher determined that the population in this study was class VIII even semester who was studying vibrations and waves. The criteria for the success of this research are an increase in the ability to master concepts and an increase in science process skills for students who study wave vibrations using a guided inquiry approach and students who study wave vibrations using the demonstration method. The results of the analysis show that the application of guided inquiry learning can improve students' mastery of concepts and science process skills on vibration and wave material, which is indicated by an increase in N-Gain. The increase in the N-Gain mastery of students' concepts for the experimental class is 58.53% and the control class is 36.29%, while the increase in science process skills for the control class students is 26.43% in the low category, while the increase in the science process skills of the experimental class students is 64.44% in the medium category. In addition, students and teachers gave positive responses to the application of guided inquiry learning